Is there an additional benefit of serial NT-proBNP measurements in patients with stable chronic heart failure receiving individually optimized therapy? - Franke, Jennifer; Frankenstein, Lutz; Schellberg, Dieter; Bajrovic, Amer; Wolter, Jan Sebastian; Ehlermann, Philipp; Dösch, Andreas; Nelles, Manfred; Katus, Hugo; Zugck, Christian (Clinical research in cardiology, 2011)
The role of serial NT-proBNP measurements in patients suffering from chronic systolic heart failure (CHF) who already receive individually optimized pharmacotherapy is still unresolved.